Development of executive system architecture of the converting class - Lutsenko, Igor; Fomovskaya, Elena; Serdiuk, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
The issue of the control purpose achievement and the related issue of optimization of technological processes are closely connected with development of the architecture of the controlled system. So, the structural optimization problem solution can lead to such architectural concept at which the solution of the problem of parametrical optimization becomes impossible in principle. Complexity of the solution of similar problems consists in the fact that for today there is no standard idea of what is a “system”, “controlled system”, “simple system”, “complex system”, etc. That is, the issue of what is generally considered as a system is conceptually unresolved. Therefore, the reference point, as a standard of a system, were the following postulates: all functions of an object have to be carried out automatically, the received object has to provide interactive interaction with other objects, the object has to carry out only one basic technological function (heating, crushing, movement, sorting, etc.). For testing the operability of architectural concepts, a specially developed program designer was used. As the result of research, the internal structure of a single-product system of the converting type has been developed. The entire set of the interconnected mechanisms is presented in the form of five subsystems. Each subsystem carries out the intrasystem function. Definition is given to a system of the converting type and its subsystems. The use of the offered architecture of the converting system creation allows using the block principle of systems creation of this class. Besides, such principle of allocation of subsystems makes them robust as at failures in the functioning of the registration and optimization subsystems they can be disconnected. At the same time, the loss of optimizing opportunities won't lead to the loss of operability of another part of the system and the entire system environment.